Solar photovoltaic based cascaded multilevel inverter with 33-levels using phase opposition disposition control method - Deepak, Chandolu Sai; Thiruveedula, Madhu Babu; Teja, Bandari Rahul; Gowtham, Supe; Vivek, Sthambhampally; Kumar, Panuganti Yeshwanth (Institute of Advanced Engineering and Science, 2025)
A cascaded multilevel inverter (MLI) tailored for photovoltaic (PV) networks, aiming to improve power quality and support transformer-less operation. The symmetric MLI design is selected for its effectiveness in minimizing harmonics and enhancing fault tolerance in high-power scenarios, where the use of power semiconductor converters can introduce complications. The proposed inverter configuration achieves thirty-three voltage levels, optimizing power quality while using insulated gate bipolar transistor (IGBT) semiconductor switches. The phase opposition disposition (POD) control method is applied to trigger necessary switching signals for the inverter's components. To ensure high output voltage for the MLI, a boost converter is employed, and the overall system is tested with an R load. The effectiveness of the design is validated through MATLAB/Simulink simulations, which demonstrate a notable reduction in total harmonic distortion (THD).